Low total cholesterol predicts early death in children with hemophagocytic lymphohistiocytosis - Xiao, Li; Xu, Ximing; Zhang, Zhiling; Dou, Ying; Guan, Xianmin; Guo, Yuxia; Yu, Jie (Frontiers in Pediatrics, 2023)
Background: Hemophagocytic lymphohistiocytosis (HLH) is a rapidly progressive and potentially life-threatening disorder. Identifying risk factors and timely adjustment of the given treatment regimens is critical to reducing the early mortality in HLH patients. Hypocholesterolemia has been reported to be associated with poor prognosis in a variety of critical illnesses. However, serum cholesterol is rarely studied in HLH patients, and its prognostic value is unclear. Methods: We conducted a retrospective cohort study in National Clinical Research Center for Child Health and Disorders (Chongqing), identifying pediatric HLH patients diagnosed with the HLH-2004 protocol and treated with immunochemotherapy between January 2008 and December 2020. The patients’ blood lipid levels at initial diagnosis of HLH, including triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein- cholesterol (LDL-C), were reviewed based on electronic medical records. Both Cox and logistic regression models were used to estimate the effects of blood lipid indicators on early death (within 30 days after diagnosis). Results: The observed 30-day mortality rate of the 353 included patients was 19.05% (64/336, 17 were lost to follow-up). The Kaplan-Meier-estimated 3-year survival rate was 61.67% (95% CI, 56.27%-67.59%). Lipid panel was performed in 349 patients: 91.98% (321/349) had TG ≥ 1.80 mmol/L, 92.84% (324/349) had HDL-C ≤1.04 mmol/L, 58.74% (205/349) had LDL-C ≤1.30 mmol/L and 24.64% (86/349) had TC ≤ 3.11 mmol/L. TC ≤ 3.11 mmol/L and BUN ≥ 7.14 mmol/L were the independent risk factors for 30-day mortality [HR(95%CI): 2.85(1.46, 5.57) and 2.90(1.48, 5.68), respectively]. Compared with the low-risk group (no risk factors present), the patients had a nearly 10-fold increased risk of early death [HR = 9.98, 95%CI: (4.23, 23.56)] in the high-risk group (two risk factors were present) and a 6-fold increased risk of early death [HR = 6.24, 95%CI: (3.18, 12.22)] in the intermediate-risk group (one risk factor was present). Conclusion: Severe derangement of lipoproteins is common in children with HLH, and decreased TC is an independent risk factor for early death. More attention needs to be paid to hypocholesterolemia during the diagnosis and management of HLH patients.